Dimensionless parameter scaling of intrinsic torque in C-Mod enhanced confinement plasmas. (12th January 2021) - Rice, J.E.; Cao, N.M.; Tala, T.; Chrystal, C.; Greenwald, M.J.; Hughes, J.W.; Marmar, E.S.; Reinke, M.L.; Rodriguez Fernandez, P.; Salmi, A.
Abstract: A dimensionless parameter dependence study of intrinsic torque has been performed on a database of H- and I-mode plasmas from the Alcator C-Mod tokamak. The torque was determined by comparing intrinsic angular momentum density profiles just before and just after L–H and L–I transitions. The intrinsic torque has been found to scale as β N 1.5 ρ * − 1.0 ν * 0.1, with the parameter ranges 0.3 ⩽ β N ⩽ 1.5, 0.004 ⩽ ρ * ⩽ 0.011 and 0.04 ⩽ ν * ⩽ 0.9. Comparison with results from JET and DIII-D suggests that the intrinsic torque should be normalized by some measure of the device size. Depending upon this normalization, the estimated total intrinsic torques for ITER, SPARC and ARC are ∼20, ∼4 and ∼8 Nm, respectively.